Modulating the function of ABCB1: in vitro and in vivo characterization of sitravatinib, a tyrosine kinase inhibitor. Issue 7 (11th June 2020) - Yang, Yuqi; Ji, Ning; Cai, Chao‐Yun; Wang, Jing‐Quan; Lei, Zi‐Ning; Teng, Qiu‐Xu; Wu, Zhuo‐Xun; Cui, Qingbin; Pan, Yihang; Chen, Zhe‐Sheng
Abstract: Background: Overexpression of ATP‐binding cassette (ABC) transporter is a major contributor to multidrug resistance (MDR), in which cancer cells acquire resistance to a wide spectrum of chemotherapeutic drugs. In this work, we evaluated the sensitizing effect of sitravatinib, a broad‐spectrum tyrosine kinase inhibitor (TKI), on ATP‐binding cassette subfamily B member 1 (ABCB1)‐ and ATP‐binding cassette subfamily C member 10 (ABCC10)‐mediated MDR. Methods: MTT assay was conducted to examine cytotoxicity and evaluate the sensitizing effect of sitravatinib at non‐toxic concentrations. Tritium‐labeled paclitaxel transportation, Western blotting, immunofluorescence analysis, and ATPase assay were carried out to elucidate the mechanism of sitravatinib‐induced chemosensitization. The in vitro findings were translated into preclinical evaluation with the establishment of xenograft models. Results: Sitravatinib considerably reversed MDR mediated by ABCB1 and partially antagonized ABCC10‐mediated MDR. Our in silico docking simulation analysis indicated that sitravatinib strongly and stably bound to the transmembrane domain of ABCB1 human‐mouse chimeric model. Furthermore, sitravatinib inhibited hydrolysis of ATP and synchronously decreased the efflux function of ABCB1. Thus, sitravatinib could considerably enhance the intracellular concentration of anticancer drugs. Interestingly, no significant alterations of both expression level and localization of ABCB1 were observed. More importantly, sitravatinib could remarkably restore the antitumor activity of vincristine in ABCB1‐mediated xenograft model without observable toxic effect. Conclusions: The findings in this study suggest that the combination of sitrvatinib and substrate antineoplastic drugs of ABCB1 could attenuate the MDR mediated by the overexpression of ABCB1.